مجلة جامعة الملك عبدالعزيز-علوم البحار 2014
DOI: 10.4197/mar.25-1.3
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Variation of Water Physicochemical Parameters and Trace Metals in Lake Manzala, Egypt

Abstract: Manzala lake is the largest costal lake east Nile Delta and is considered as one of the most dynamic ecosystems along the Egyptian coast on the Mediterranean Sea. It is ecologically and economically important due to biological diversity, valuable fish, and wild life resources. The lake has undergone a considerable reduction in surface area due to input from human activities. This costal Lake constitutes an estuarine environment with a very particular behavior. The purpose of this investigation is to measure th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
4

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 9 publications
0
5
4
Order By: Relevance
“…Research suggests that an increase in silicate concentration corresponds approximately with that in phosphate concentration (Heron, ). Contrary to our findings, El‐Saharty () found a reduction in phosphate concentration during the autumn, due to an increase in uptake of phosphate by phytoplankton. P was decreased due to the presence of phytoplankton in a study by Sierp and Qin ().…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Research suggests that an increase in silicate concentration corresponds approximately with that in phosphate concentration (Heron, ). Contrary to our findings, El‐Saharty () found a reduction in phosphate concentration during the autumn, due to an increase in uptake of phosphate by phytoplankton. P was decreased due to the presence of phytoplankton in a study by Sierp and Qin ().…”
Section: Discussioncontrasting
confidence: 99%
“…The seasonal fluctuations of trace elements can largely be credited to environmental factors, including temperature, evaporation and rainfall and plankton dynamics (Adhikari & Ayyappan, 2004;Dickson, 1975;Gibson, Wang, & Foy, 2000;Hecky, Kling, & Brunskill, 1986;Kimball, 1973;Sierp & Qin, 2001; Zhang et al, 2013). Farming practices, such as liming, water sources, feeding, fertilization, harvesting, cleaning the pond bottom soil at harvest and overnight drying, may also have an effect (Abu Hena et al, 2018;Adhikari, 2003;Borg, Ek, & Holm, 2001;Boyd, 1997;Christos, Miltiadis, & Theodore, 2018;El-Saharty, 2014;Shaked, Erel, & Sukenik, 2004). Furthermore, the fluctuations in plankton abundance and phytoplankton species diversity (Table 2) can relate to changes in the concentrations of trace elements, sunlight hours and temperature (Calijuri, Santos, & Jati, 2002;Sommer et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The comparison of water quality physico-chemical parameters and major dissolved ions in this study and those of previous studies in Bahr El-Baqar drain, Lake Manzala and the River Nile are reported in Table 3. It is concluded that the average value of pH (7.48) in this study is higher than (6.6-7.35) previously reported in the water of Bahr El-Bagar and Kitchener drains [12,18,20], while it is lower than those of [1,5,7,11,16,25,[27][28][29][30][31]33] (Table 3). The average TDS (1685.8 mg/L) in the drain water is higher than (2.8-1485 mg/L) repored before [5,12,[29][30]33], however, it is below those of [1,16,[27][28] (Table 3).…”
Section: Seasonal and Spatial Variation Of Physicochemical Parameters...contrasting
confidence: 65%
“…It is concluded that the average value of pH (7.48) in this study is higher than (6.6-7.35) previously reported in the water of Bahr El-Bagar and Kitchener drains [12,18,20], while it is lower than those of [1,5,7,11,16,25,[27][28][29][30][31]33] (Table 3). The average TDS (1685.8 mg/L) in the drain water is higher than (2.8-1485 mg/L) repored before [5,12,[29][30]33], however, it is below those of [1,16,[27][28] (Table 3). The average EC (2864 μS/cm) in the drain water is much higher than (276-2500 μS/cm) in most previous studies [1,5,12,18,20,29,[32][33], while it is lower than those of [11,16,31].…”
Section: Seasonal and Spatial Variation Of Physicochemical Parameters...contrasting
confidence: 65%